2011
DOI: 10.1590/s0100-29452011005000077
|View full text |Cite
|
Sign up to set email alerts
|

Modo de reprodução e viabilidade de pólen de três espécies de jabuticabeira

Abstract: RESUMO -O objetivo deste trabalho foi determinar o modo de reprodução e as condições para testes de viabilidade in vitro de pólen de três espécies de jabuticabeira (Plinia cauliflora, P. trunciflora e P. jaboticaba). Avaliaram-se a frutificação efetiva em ramos ensacados e não ensacados, e aspectos da morfologia floral. A viabilidade de pólen foi avaliada em meio de cultura com e sem ácido bórico, com pólen coletado em diferentes períodos após antese. A germinação de pólen de seis genótipos foi quantificada an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
6
0
4
Order By: Relevance
“…The jabuticaba trees, belonging to the Myrtaceae family, are comprehended in nine species, among which there is the jabuticabeira of cabinho [Plinia trunciflora (DC) Berg], which presents natural occurrence in the Southwestern Region of Paraná state (Danner et al, 2011b) and altitude regions.…”
Section: Introductionmentioning
confidence: 99%
“…The jabuticaba trees, belonging to the Myrtaceae family, are comprehended in nine species, among which there is the jabuticabeira of cabinho [Plinia trunciflora (DC) Berg], which presents natural occurrence in the Southwestern Region of Paraná state (Danner et al, 2011b) and altitude regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the pollinators and floral, reproductive biology of the species were not found in the literature. These are essential for the understanding of the ecological relations between different species, the conservation of the germplasm, the elaboration of management protocols in cultivation and the beginning of breeding programs (Torres & Galetto, 2011;Danner, Citadin, Sasso, Sachet, & Malagi, 2011a;Françoso, Guaraldo, Prada, Paiva, Mota, & Pinto, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The jabuticatree belongs to Myrtaceae family and to the genus Plinia, being a native fruit tree of Brazil, with nine well-known species, among which stands out the 'jabuticatree paulista' or 'jabuticatree-açu' [Plinia cauliflora (DC.) Berg], being one of the most sold species in the Brazilian South market (Danner et al, 2011a). This species presents desirable sensory characteristics that allow its 'in natura' commercialization or with processing techniques, generating jellies and fermented beverages (Sasso et al, 2010).…”
Section: Introductionmentioning
confidence: 99%